Motives and consequences of revolution from siyasah shar'iyyah: Algerian scholars’ perceptionon contemporary Arab revolutions / Aziez Salah Eddine - Aziez , Salah Eddine (2018)
This study examines the revolution in Islam in general and the Arab Spring revolution in particular. It discusses the definition of revolution and the motives that sparked the Arab Spring revolution and its similarity with the motives of revolution in Islamic history.This study also dealt with the most important qualities that characterized the revolutions of the Arab Spring and its compatibility with Maqasid al-Syariah in its consequences.Using the statistical method, this research also examines the legitimacy of the revolution in terms of its motives and realities and consequences to topple a government on the views of Algerian scholars who are the respondents of this study. Based on the method, the researcher also assess the understanding of the respondents on maqasid al-syariah in the field of politics. In this study, the researcher applied the inductive historical method and then followed by the descriptive survey methodology, which is related to the study of a contemporary phenomenon with the intention of describing and interpreting it. Using statistical methods, the findings from the survey of respondents show that the Arab Spring revolution has several motives; the religious motives as the finding shows that it has a weak tendency, political motives which the finding shows to have strong tendencies, and socio-economic motives that the findings shows to have the strongest tendencies. Through statistical methods as well, researcher found that the Arab Spring was dominated by the demagogic character instead of wisdom, because it clearly does not have a strong political leadership and is not spared from the effects of damage and harm.Researcher also found that the Arab Spring revolution was influenced by emotions without taking into account the rational factors caused by the influence of the media that spread it. And this study illuminate that the Arab Spring revolution also did not compatible with the Maqasid al-Syariah in its consequences.Most respondents are of the view that the Arab Spring revolutions have had a negative impact on religious, social and economic levels, and if there any positive impact, it is only a little as they encouraged it at the beginning. The findings also show that the Arab Spring revolutions has further strengthened the influence of Western powers on Muslim countries,which proves there was a weakness in 'Fiqh Maalat' among the Islamic scholars in relation with issues involving the political field.